Phosphenes and the effects of charged particles on the visual system - Carozzo, Simone; Sannita, Walter G. (Frontiers in Neurology, 2025)
ObjectiveReview the evidence from space travel crews, early and recent experiments in particle accelerators, and observations in patients undergoing heavy ions treatments for tumors of the eye or skull that charged particles act on the visual system triggering the perception of phosphenes.ResultsThe visual effects of charged particles are multi-modal in origin, act differently on the retina photoreceptors and neurons, and indicate a peculiar sensitivity to charged particles of the visual system. Acute toxicology in heavy ion treatment has been documented and should be differentiated by quasi-physiological actions.SignificanceThe potential relevance of phosphenes as indicative of functional impairment stands as a possible variable in hadron-therapy, the proper monitoring of which may contribute to optimizing the treatment procedures and in the prediction of outcome.